1985
DOI: 10.1172/jci112132
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand's disease with spontaneous platelet aggregation induced by an abnormal plasma von Willebrand factor.

Abstract: We have investigated and characterized the abnormalities in four unrelated patients with von Willebrand's disease (vWd) who have (a) enhanced ristocetin-induced platelet aggregation (RIPA) at low ristocetin concentrations, (b) absence of the largest plasma von Willebrand factor (vWf) multimers, and (c) thrombocytopenia. The platelet-rich plasma of these patients aggregates spontaneously without the addition of any agonists. When isolated normal platelets are resuspended in patient plasma spontaneous aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…Large multimers are synthesized normally, as confirmed by the normal platelet VWF content seen in type 2B VWD, but currently cannot be detected in vivo for their removal. Enhanced ristocetininduced platelet aggregation (RIPA), spontaneous platelet aggregation (SPA) [14][15][16] and sometimes thrombocytopenia are also part of the type 2B VWD phenotype. 17 Thrombocytopenia may be persistent or transient but is commonly worse after DDAVP infusion, pregnancy, exercise or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Large multimers are synthesized normally, as confirmed by the normal platelet VWF content seen in type 2B VWD, but currently cannot be detected in vivo for their removal. Enhanced ristocetininduced platelet aggregation (RIPA), spontaneous platelet aggregation (SPA) [14][15][16] and sometimes thrombocytopenia are also part of the type 2B VWD phenotype. 17 Thrombocytopenia may be persistent or transient but is commonly worse after DDAVP infusion, pregnancy, exercise or surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The disorder was named Montreal platelet syndrome (MPS). 2 Several studies have now shown that some patients with type 2B von Willebrand disease (VWD) present with macrothrombocytopenia [4][5][6][7][8] and spontaneous platelet aggregation in vitro, [4][5][6][7]9 features found in MPS. 10 A diagnosis of type 2 VWD is suggested by a discrepantly low ristocetin cofactor activity (VWF:RCo) compared with the VWF antigen (VWF:Ag; [VWF:RCo/VWF:Ag ratio Ïœ 0.7]).…”
Section: Introductionmentioning
confidence: 99%
“…The affected patients also exhibit absence of the largest vWF multimers in plasma, probably owing to their spontaneous binding to circulating platelets (7). In some cases, this interaction may induce in vivo platelet aggregation and thrombocytopenia (8,9), which always occur in type IIB von Willebrand disease after administration of 1-deamino-8-D-arginine vasopressin (DDAVP)' (10). Different gene mutations have been identified in a number ofthese patients (3,(11)(12)(13) and all have been found to be localized in a domain of vWF, the disulfide loop created by the linkage of Cys5" and Cys695, that has been indicated as an important element in the regulation of vWF binding to GP lb (2,3).…”
Section: Introductionmentioning
confidence: 99%